Resolva as equações abaixo, observando cada conjunto Universo:
7) 3 (x+1)+2 (2x-3)=5 (x-1)+8; U=Q
8) 3-7 (1-2x)=5-(x+9); U=Q
9) (1+3x)-(1-2x)+(-11-7x)=5; U=Z
10) 2 (2x+7)+3 (3x-5)=3 (4x+5)-1; U=Q
11) x-3 (4-x)=7x-(1-x); U=Z
12) 2 (1-5x)+3 (-1-x)-4 (-7+2x)=-x; U= Z
13) 5 (2x+7)-1=4 (x-5)+9; U=Z
14) 2 (x-1)+3 (x+1)=4 (x+2); U=Q
15) 2 (2x+3)+5 (x-1)=8-3 (x-1); U=Z
Respostas
respondido por:
0
7) 3 (x+1)+2 (2x-3)=5 (x-1)+8; U=Q
3x +3 +4x -6 = 5x -5 +8
2x = 6
x = 6/2
x= 3
8) 3-7 (1-2x)=5-(x+9); U=Q
3 -7 +14x = 5 -x -9
13x = 0
9) (1+3x)-(1-2x)+(-11-7x)=5; U=Z
10) 2 (2x+7)+3 (3x-5)=3 (4x+5)-1; U=Q
4x +14 +9x -15= 12x +15 -1
x =15
11) x-3 (4-x)=7x-(1-x); U=Z
x -12 +3x = 7x -1 +x
-4x = 11
4x = -11
x = -11/4
12) 2 (1-5x)+3 (-1-x)-4 (-7+2x)=-x; U= Z
13) 5 (2x+7)-1=4 (x-5)+9; U=Z
10x +35 -1 = 4x -20 + 9
6x = - 45
x = -45/6
14) 2 (x-1)+3 (x+1)=4 (x+2); U=Q
15) 2 (2x+3)+5 (x-1)=8-3 (x-1); U=Z
3x +3 +4x -6 = 5x -5 +8
2x = 6
x = 6/2
x= 3
8) 3-7 (1-2x)=5-(x+9); U=Q
3 -7 +14x = 5 -x -9
13x = 0
9) (1+3x)-(1-2x)+(-11-7x)=5; U=Z
10) 2 (2x+7)+3 (3x-5)=3 (4x+5)-1; U=Q
4x +14 +9x -15= 12x +15 -1
x =15
11) x-3 (4-x)=7x-(1-x); U=Z
x -12 +3x = 7x -1 +x
-4x = 11
4x = -11
x = -11/4
12) 2 (1-5x)+3 (-1-x)-4 (-7+2x)=-x; U= Z
13) 5 (2x+7)-1=4 (x-5)+9; U=Z
10x +35 -1 = 4x -20 + 9
6x = - 45
x = -45/6
14) 2 (x-1)+3 (x+1)=4 (x+2); U=Q
15) 2 (2x+3)+5 (x-1)=8-3 (x-1); U=Z
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás